Pectin Extraction From The Skin Of Lime (Citrus aurantifolia) With Variety Of Orange Skin Color - Miranti Mangansige; Thelma D. J. Tuju; Christine F. Mamuaja (Jurnal Agroekoteknologi Terapan, 2022)
Pectin is one of polymer compounds which has a lot advantages, such as binding water, forming gels, or thickening liquid. This compound usually used as a raw material of various derived products of foods and pharmaceuticals as well, commonly found in flavedo, albedo, and edible parts in lime. Pectin is solid and has a white-brownish color. The other physical properties such as solubility, viscosity, and gel-forming ability depend on its chemical characteristics of the pectin itself such as methoxyl levels, degree of esterification. Pectin is widely used in food products as an emulsifying agent. The use of pectin is also widely found in the jam and jelly industry. Pectin can also be obtained from a wide variety of orange peels by means of extraction. In the present study, Complete Randomized Design method was performed with one factor, namely the difference in lime peel color; therefore, there were two treatments and three repetitions obtained. The parameters analyzed were pectin amendments, methoxyl levels. Moisture content, ash content. Based on the results of the analysis in this study, the best level of maturity is the green lime peel with an average value of pectin amendment of 34,6 %, water content of 9,01 %, ash content of 2,18 %, methoxyl content of 5,341 % Keywords : Extraction, pectin, lime peel Abstrak Pektin merupakan senyawa polimer, yang dapat mengikat air, membentuk gel, atau mengentalkan cairan. Pektin juga merupakan polisakarida yang digunakan sebagai material fungsional dalam pangan dan farmasi, dapat ditemukan melimpah dalam flavedo, albedo dan porsi edible dari jeruk nipis. Pektin berbentuk padatan yang berwarna putih kecoklatan. Sifat fisika lainnya seperti kelarutan, viscositas, dan kemampuan membentuk gel tergantung dari karakteristik kimia pektin itu sendiri seperti kadar metoksil, derajat esterifikasi. Pektin banyak digunakan dalam prosuk-produk pangan sebagai zat pengemulsi. Penggunaan pektin juga banyak dijumpai pada industry selai dan jeli. Pektin juga dapat diperoleh dari berbagai macam kulit jeruk dengan cara di ekstraksi. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL) Dengan perlakuan tiga variasi warna kulit jeruk nipis ( Citrus Aurantifolia) dengan tiga kali pengulangan. Parameter yang dianalisa adalah Rendemen pektin, Kadar air, Kadar abu, Kadar metoksil. Berdasarkan hasil analisa, nilai rata-rata rendemen pektin adalah 34 %, nilai rata-rata Kadar air pektin adalah 9,01%, dan nilai rata-rata kadar abu pektin adalah 2,18 %, sedangkan Kadar Metoksil pektin adalah 5,341 %. Kata Kunci: Ekstraksi, pektin, kulit jeruk